Parents and teachers’ perceptions of online music sessions for children with autism during the COVID-19 pandemic in Malaysia: an exploratory feasibility study - Lee Shi Min, Abi; Selvarajah, Indra (Human Resource Management Academic Research Society, 2023)
Autism is a neurological disorder that manifests as social communication skill limitations, fixated interests and rigid behaviours. During the COVID-19 pandemic in Malaysia, online lessons became the norm and it transformed the way teachers and parents collaborated to ensure that children with autism continued to receive education from home. However, parents of autistic children noticed a marked regression in basic living skills and communication skills in their children during the pandemic. The importance of music has been indicated by a growing body of research as it can help children with autism maintain and develop social and communication skill. While research during the pandemic revealed that children with autism’s age, cognitive functioning, family income, parent education and cultural background are factors that may influence treatment selection and outcomes, parents and teachers’ positive and negative perceptions of online learning experiences with the child may also contribute to it. The purpose of this exploratory study was to gauge the perceptions of parents and teachers towards online education in order to determine the feasibility of introducing music therapy-based online music classes for children with autism as a potential means to promote and preserve their social and communication skills. A total of 59 teachers and 69 parents participated in this study by answering a prepared online survey questionnaire through Google Docs. The findings were analysed using conventional content analysis and later with descriptive statistic on SPSS. The findings from this study indicated that parents are more interested in having online music sessions with their children compared to teachers. Teachers are less interested due to the lack of musical skill to deliver quality online sessions with music. Based on parents and teachers’ overall perceptions, this study found that children with autism had the potential to benefit from online music lessons aimed at stimulating social and communication skills. However, this study also found that both parents and teachers needed training in the use of technology to increase their confidence in using online platforms. Futher research is needed to develop a suitable coaching model to equip both parents and teachers in assisting autistic students during online music lessons.